Development and validation of the Online Learning Self-efficacy Scale (OLSS): A structural equation modeling approach. Issue 3 (3rd July 2021) - Sun, Yan; Rogers, Reenay
ABSTRACT: This study reports the development and validation of the Online Learning Self-efficacy Scale (OLSS) for online students. The original 73 OLSS items, developed through a comprehensive review of literature and a content and validity review process by a panel of education graduate students and faculty members, were sent out through a survey to the online students in a university in the southern region of the United States. The data from 366 online students who responded to the survey were analyzed using exploratory and confirmatory factory analyses with a structural equation modeling approach. The final validated OLSS consists of 31 items loading on four factors: Technology use self-efficacy (TU); Online learning task self-efficacy (OLT), Instructor and peer interaction and communication self-efficacy (IPIC), and Self-regulation and motivation efficacy (SRM). Cronbach's α ranged between 0.866 and 0.948 indicating high internal consistency reliability for the OLSS.